The Effect of Aggregate Gradation Variation on Mechanical Performance and Porosity of Porous Geopolymer Concrete - Saputro, Yayan Adi; Qomaruddin, Mochammad; Budianta, Tarsisius Dwi Wibawa (Journal of Green Science and Technology, 2025)
Porous geopolymer concrete has gained attention as a sustainable and environmentally friendly alternative to conventional Portland cement-based concrete, utilizing industrial waste such as fly ash. This study investigates the effect of aggregate gradation variations on the mechanical properties, porosity, and sustainability of fly ash-based porous geopolymer concrete. The experimental method was employed, utilizing fly ash as the primary binder, sodium hydroxide (NaOH) as the activator, and coarse aggregates of varying sizes (3/8", 1/2", and 3/4"). The concrete samples were tested for compressive strength and porosity at 7, 14, and 28 days following ASTM standards. The results indicate that aggregate gradation significantly influences the mechanical properties, porosity, and sustainability of geopolymer concrete. Smaller aggregate sizes (3/8") produced higher compressive strength (5.42 MPa at 28 days) but lower porosity, while larger aggregates (3/4") increased porosity but reduced compressive strength. Additionally, the study confirms that geopolymer concrete using fly ash as a binder meets the standard requirements for setting time, specific gravity, and durability. These findings contribute to optimizing porous geopolymer concrete for sustainable construction applications, particularly in drainage and permeable pavement systems, promoting waste utilization and environmental sustainability.  Keyword: Porous geopolymer concrete, fly ash, , porosity, waste, sustainability